Impact of global warming on Potential Years of Life Lost by cardiopulmonary diseases in Brazilian capital cities - Jacobson, Ludmilla da Silva Viana; Oliveira , Beatriz Fátima Alves de; Perez, Letícia Palazzi; Hacon, Sandra de Souza (Sustainability in Debate, 2020)
This study aims at assessing the future impact of global warming in the Potencial Years of Life Lost (YLL) for cardiovascular diseases in adults (â‰¥45 years) and respiratory diseases in the elderly (â‰¥60 years). This is an ecological study, which includes all the capitals of Brazil. Future projections used temperature data sourced from the Eta-HadGEM2S Regional Model for the RCP8.5 scenario. YLL fractions attributable to temperature were estimated for global warming scenarios of 1.5°C, 2.0°C, and 4.0°C. The results showed that, in absolute numbers, Rio de Janeiro and São Paulo have presented the largest YLL contribution attributable to global warming among the capital cities. Campo Grande and Cuiabá were the most impacted capitals by a global warming of 1.5ºC compared to the baseline period (1961-2005), both for respiratory diseases in the elderly and for cardiovascular diseases in adults. Results of this research suggest that the impact of exposure to temperature on YLL tends to increase as the level of global warming increases.